Wymiana handlowa jako czynnik postępu cywilizacyjnego w teorii Józefa Supińskiego - Szymański, Zdzisław (Wydział Prawa i Administracji UAM, 1996)
Scientific works of Józef Supiński (1804 - 1893), i.e. Myśl ogólna fizjologii wszechświata (General concept of universal physiology, Lwów 1860) and Szkoła polska gospodarstwa społecznego (Polish school of social economics, Lwów 1862, 1865) were issued in late romanticism period. They had been inspired and, in the same time, were a reaction to Filozofia ekonomii materialnej ludzkiego społeczeństwa (Philosophy of material economy of human society) by Henryk Kamieński (iisued in Poznań, 1843 and 1845). Philosophical and social conceptions of H. Saint-Simon played here also an important part. Following Kamieński Supiński stresses civilizational role of commercial exchange and its favourable influence on increase of the volume of production and social wealth. Being human creation this exchange brings leads social relations to perfection and eliminates by the way all forms of violence. It is also a binding agent uniting individuals into a society. Supiński discusses some categories of market ekonomy: money and credit, and first of all - the concurrence meant as emulation or contest. Analogically to H. Kamieński he also creates a deductively sophisticated model of free concurrence. This model is approached now by economies of highly developped Western European countries. Among disbalancing factors he cites: lack of full information on the production volume of a given produck within global scale and, on the other hand, on buyers' preferences, as well as different level of innovations' application.
Commercial exchange as a factor of civilizational progress in the theory of Józef Supiński